RANCANG BANGUN APLIKASI PENCATATAN IBADAH NAFSIYAH MAHASISWA STIKOM EL RAHMA BERBASIS ANDROID - Ridho Practyo, Bagus Wahyu Pandhito, Dwi Susanto (Jurnal Teknorama (Informatika dan Teknologi El Rahma), 2024)
Abstract This research aims to implement Android-based Information Systems technology for recording spiritual activities at STIKOM El Rahma. Employing the Research and Development (R&D) method and the Rapid Application Development (RAD) model, this study seeks to optimize technology application and address existing issues at STIKOM El Rahma. The system is developed using PHP 8.3 and CodeIgniter 3, and is designed to facilitate the management of spiritual activity records. The results of this research demonstrate that the system is effective and successful in applying information technology to the recording of spiritual activities at STIKOM El Rahma.